Bioinspired Cementitious Materials: Main Strategies, Progress, and Applications - Shahsavari, Rouzbeh; Hwang, Sung Hoon (Frontiers in Materials, 2020)
Nature-inspired ensemble of organic and inorganic constituents, such as that found in the microstructure of nacre and dactyl clubs of Mantis shrimp, has evolved into the model system for the structural design of industrial composites. This novel design concept, which helps attaining the balance between strength, toughness and ductility, has not only induced a paradigm shift in the synthesis of advanced materials such as graphene-based composites but also, in the development of more abundant, low-cost materials such as cement and concretes. The advance in synthetic techniques and the advent of new manufacturing technologies such as 3D printing has enabled effective integration of cementitious materials with soft materials across various length scales. Furthermore, novel functional properties such as self-healing have also been materialized based on a variety of strategies. This review will provide a comprehensive overview on the ongoing research efforts, encompassing 3D printing, self-healing strategies and integration of cement hydrate with organic components, all of which are actively exploited in synthesizing bioinspired, multifunctional cementitious materials.